Psychological stress and depression symptoms in nursing undergraduates: the chain mediating effect of cognitive reappraisal and ruminate thinking - Yinjuan Zhang; Fang Liu; Jin Ma; Jing Wu; Chao Shen; Fengjiao Chang; Wendong Hu; Hongjuan Lang (BMC Nursing)
Abstract Background Nursing students exhibit a higher incidence of mental disorders. Studies have identified psychological stress contributes to elevated depression symptoms through reappraisal cognitive in nursing students. However, there is little research exploring the knowledge regarding the role of ruminative thinking in mediating the associations between psychological stress and depression symptoms. Guiding by the non-hemostatic model and cognitive control theory, the study aims to investigate the chained mediation of cognitive reappraisal and ruminate thinking between psychological stress and depression symptoms among nursing undergraduates. Methods A total of 1,220 nursing undergraduates were carried out by stratified sampling from July to December of 2023 via online survey. The investigation adopted the Perceived Stress Scale (PSS-10), Emotion Regulation Questionnaire (ERQ), Ruminative Response Scale (RRS), and the Center for Epidemiologic Studies Depression Scale (CES-D) to measure the level of psychological stress, cognitive reappraisal, ruminative thinking and depression symptoms, respectively. Pearson’s r was utilized to investigate the interrelationships, and the structural equation model (SEM) was used to clarify the mediation effects among the four variables. Results The mean total score of CES-D was 21.57 ± 10.79. SEM analysis proved that psychological stress had a direct positive effect on depression symptoms (β = 0.388). accounting for a substantial 51.52% of the total effect. Cognitive reappraisal and ruminate thinking partially mediated the association between psychological stress and depression symptoms (95% CI: 0.094–0.210), and the mediating effect accounted for 48.48% of the total effect. Conclusions Nursing students exhibited a high prevalence of depression, and cognitive reappraisal and ruminate thinking partially mediated the correlations between psychological stress and depression symptoms. Interventions targeting at consolidating cognitive reappraisal and ruminate thinking are imperative for improving depression.